Community-Based Assessment of Knowledge, Attitude, Practices and Risk Factors Regarding COVID-19 Among Pakistanis Residents During a Recent Outbreak: A Cross-Sectional Survey - Afzal, Muhammad Sohail; Khan, Aisha; Qureshi, Ubaid Ur Rahman; Saleem, Sadia; Saqib, Muhammad Arif Nadeem; Shabbir, Rana Muhammad Kamran; Ahmed, Haroon (Springer, 2021)
Exceptional precautionary measures have been adopted to stop the transmission and control of COVID-19 through the world and Pakistan is facing lockdown in this scenario. Public loyalty to precautionary measures is affected by their knowledge, attitude, risk factors and practices (KAP) towards COVID-19. The present study was conducted among the Pakistani residents to observe the knowledge, attitude, practices and risk factors towards COVID-19 outbreak in Pakistan. A questionnaire was designed, and a cross-sectional survey was conducted among participants of the study area. Participants were asked the questions regarding knowledge, attitude, practices and risk factors towards COVID-19. Data were analyzed by SPSS andt/Ftest and correlation was applied among the knowledge, attitude, risk factors and practices. A total of 1060 questionnaires were received. 1004 were included while 56 were excluded. The highest representation was from Punjab province (65.6%), female (63%) and age group of 21-30 years (62.1%). Most participants were single (85%), Muslim (99.4%), Urdu speaking (45.6%) and were graduates (51.5%). Most of the participants were students (52.9%) and were from economically middle-class families (40.8%). The knowledge was positively correlated with attitude and practices whereas negatively correlated with risk factors (P < 0.05). The attitude was negatively correlated with risk factor and positively correlated with practices. The risk factors and practices were positively correlated with each other. Health education program to improve the COVID-19 knowledge, attitude, practices and risk factors should be initiated to combat current health challenge.
Keywords: COVID-19; Knowledge; Attitude; Practices; Correlation; Pakistan